(3eNJUQ GdeSJaGO aj JGQjN HZOGOs - (3LHQGFjd MfhT CUaQs; (3GdNWjH GdHZOGOj , CHh HcQ CMeO Hf Ydj Hf KGHJ GdNWjH GdHZOGOj,J (B463 (3g` s
(3ChdgG (B:s
(3hHYO Efg deG cGf Yde GdJGQjN cVQHI dGRH hcGf Gdhbha Ydi JGQjN HZOGO Ydi MOJg eeG jJhb Edjg CgGdi gPg GdHdGO s
(3BNQgG (B:s
(3Sd GdfhGLY Yf cQHj hJYPjHj ai MH eQgaI HjVGA QYHhH hgj WhjdI s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B377 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs